Observations of ion‐neutral coupling associated with strong electrodynamic disturbances during the 2015 St. Patrick's Day storm. Issue 1 (30th January 2017) - Zhang, Shun‐Rong; Erickson, Philip J.; Zhang, Yongliang; Wang, Wenbin; Huang, Chaosong; Coster, Anthea J.; Holt, John M.; Foster, John F.; Sulzer, Michael; Kerr, Robert
Abstract: We use incoherent scatter radar observations at Millstone Hill (MHO) and Arecibo (AO) and topside ionosphere in situ Defense Meteorological Satellite Program (DMSP) observations during the great geomagnetic storm on 17–18 March 2015 to conduct a focused study on ion‐neutral coupling and storm time ionosphere and thermosphere dynamics. Some of these observations were made around the time of large ionospheric drifts within a subauroral polarization stream (SAPS). During the storm main phase, we identify multiple disturbance characteristics in the North American late afternoon and dusk sector. (1) Strong subauroral westward drifts occurred between 20 and 24 UT near MHO, accompanied by a storm enhanced density plume passage over MHO in the afternoon with a poleward/upward ion drift. The strongly westward flow reached 2000 m/s speed near the poleward plume edge. (2) Prompt penetration electric field signatures, appearing as poleward/upward ion drifts on the dayside over both MHO and AO, were consistent with DMSP vertical drift data and contributed to plume development. (3) Meridional wind equatorward surges occurred during daytime hours at MHO, followed by 2–3 h period oscillations at both MHO and AO. The zonal electric field at AO was strongly correlated with the wind oscillation. (4) Large ion temperature enhancements as well as 50+ m/s upward ion drifts throughout the E and F regions were observed during the SAPS period. These were presumably caused by strong frictional heating due to large plasma drifts. The heating effects appeared to drive significant atmospheric upwelling, and corresponding ion upflow was also observed briefly. This study highlights some of the important effects of fast plasma transport as well as other disturbance dynamics on ion‐neutral coupling during a single intensification period within a great geomagnetic storm. Key Points: Multiple strong ion‐neutral coupling effects appeared within a few hours of SAPS during a single intensification of a great magnetic storm Strong ion‐neutral frictional heating accompanied by large atmospheric upwelling, with ion upwelling as a potential source of ion upflow Oscillating electric fields accompanied large scale storm time traveling atmospheric disturbances